Pengaruh Online Customer Rating Dan Customer Reviews Terhadap Keputusan Pembelian Pada Marketplace Shopee: Studi Kasus Mahasiswa PTN Meulaboh, Aceh Barat - Ashari, Harisna; Chairiyaton (PT. Karya Inovatif Nusantara, 2025)
This research aims to test and analyze whether online customer ratings and customer reviews influence purchasing decisions on the Shopee marketplace. The population of this study were students at PTN Meulaboh, West Aceh. The sample was determined using a purposive sampling technique based on the Lemeshow formula to obtain a sample size of 96 respondents. Data was collected by distributing questionnaires and then analyzed using multiple linear regression. The results of this research show that partially online customer ratings do not have a positive and significant effect on purchasing decisions as obtained by the sig value. of 0.128>0.05 and the calculated t value < ttable (0.535 <1.985). Furthermore, customer reviews partially have a positive and significant effect on purchasing decisions where the t-count value of the customer reviews variable (X2) is 5,811 greater than the t table value (5,811 <1.985) and the sig value. 0.000<0.05. Then simultaneously online customer ratings and customer reviews together have a positive and significant effect as seen from the calculated f test of 48,389 and f table of 3.094 (48,389>3.094) and the sig value. 0.000>0.05. Then look at the Adjusted R Square value of 0.499 or 49%, the remaining 51% is explained by other factors outside this variable.